Variation in Alpine Plant Diversity and Soil Temperatures in Two Mountain Landscapes of South Patagonia - María Vanessa Lencinas; Rosina Soler; Juan Manuel Cellini; Héctor Bahamonde; Magalí Pérez Flores; Lucas Monelos; Guillermo José Martínez Pastur; Pablo Luis Peri (Diversity, 2021)
Alpine environments and their temporal changes are rarely studied at high latitudes in the southern hemisphere. We analyzed alpine plants, soil temperatures, and growing-season length in mountains of two landscapes of South Patagonia (46° to 56° SL): three summits (814–1085 m a.s.l) surrounded by foothill grasslands in Santa Cruz province (SC), and four summits (634–864 m a.s.l.) in sub-Antarctic forests of Tierra del Fuego province (TF). Sampling followed the protocolized methodology of the Global Observational Research Initiative in Alpine Environments (GLORIA). Factors were topography (elevation and cardinal aspect) and time (baseline vs. re-sampling for plants, five annual periods for temperatures), assessed by univariate and multivariate tests. Plant composition reflected the lowland surrounding landscapes, with only 9 mountain species on 52 totals in SC and 3 on 30 in TF. Richness was higher in re-sampling than baseline, being assemblages more influenced by aspect than elevation. Mean annual soil temperature and growing-season length, which varied with topography, were related to the Multivariate El Niño Southern Oscillation Index (MEI) but did not show clear warming trends over time. We highlight the importance of long-term studies in mountainous regions of extreme southern latitudes, where factors other than warming (e.g., extreme climate events) explain variations.